Landscape- and Local-Scale Actions Are Essential to Conserve Regional Macrophyte Biodiversity - Akasaka, Munemitsu; Higuchi, Shinsuke; Takamura, Noriko (Frontiers in Plant Science, 2018)
Regional-scale pond diversity is supported by high variation in community composition. To effectively and efficiently conserve pond regional diversity, it is essential to recognize the community types in a focal region and the scales of the factors influencing the occurrence of respective community types. Based on a flora survey and GIS analysis of 367 ponds in western Japan, we developed a multinomial regression model that describes the relationship between aquatic macrophyte community type (based on cluster analysis) and five environmental factors that differ in the spatial scale at which they operate (i.e., landscape or local scale) and origin (i.e., natural or anthropogenic). A change in topographic configuration resulted in a transition of the community types with high species richness. Increasing urban and agricultural area around ponds resulted in a decrease in species-rich community occurrence; an increase in urban area increased the probability of a pond having no macrophytes, whereas that of paddy field increased the probability of a pond having only a few macrophytes. Pond surface area and proportion of artificial embankment significantly defined the pond community: greater embankment proportions increased the probability of ponds having few or no macrophytes. Our results suggest that conserving regional pond biodiversity will require actions not only at a local scale but also at a sufficiently large spatial scale to cover the full gradient of topographic configurations that influence the macrophyte species composition in ponds.